#### Answer

-84

#### Work Step by Step

(-2)(-7)(1)(3)(-2)
(-2)(-7) = 14
(1)(3) = 3
(14)(3) = 42
42(-2) = -84

Published by
Brooks Cole

ISBN 10:
1285199197

ISBN 13:
978-1-28519-919-1

-84

(-2)(-7)(1)(3)(-2)
(-2)(-7) = 14
(1)(3) = 3
(14)(3) = 42
42(-2) = -84

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.